2017
DOI: 10.1038/ncomms15040
|View full text |Cite
|
Sign up to set email alerts
|

Joint morphogenetic cells in the adult mammalian synovium

Abstract: The stem cells that safeguard synovial joints in adulthood are undefined. Studies on mesenchymal stromal/stem cells (MSCs) have mainly focused on bone marrow. Here we show that lineage tracing of Gdf5-expressing joint interzone cells identifies in adult mouse synovium an MSC population largely negative for the skeletal stem cell markers Nestin-GFP, Leptin receptor and Gremlin1. Following cartilage injury, Gdf5-lineage cells underpin synovial hyperplasia through proliferation, are recruited to a Nestin-GFPhigh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(176 citation statements)
references
References 47 publications
7
169
0
Order By: Relevance
“…Chondrocyte cloning has been well documented in the past, but this is typically associated with later stages of disease progression;2 RCGD 423 significantly increased rates of EdU incorporation, and it will be critical in future work to determine the molecular identity of these cells as well as to address the relative contributions of proliferation versus anticatabolic effects to the reduction in cartilage degeneration supported by RCGD 423. Moreover, given the decrease in proliferation elicited by the compound at 6 weeks postinjury, it will be important to ascertain if cells capable of responding are limited in the number of divisions they can undergo as this would suggest that other cell types such as synovium43 may need to be harnessed for cartilage repair or that a therapeutic window exists for potential intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocyte cloning has been well documented in the past, but this is typically associated with later stages of disease progression;2 RCGD 423 significantly increased rates of EdU incorporation, and it will be critical in future work to determine the molecular identity of these cells as well as to address the relative contributions of proliferation versus anticatabolic effects to the reduction in cartilage degeneration supported by RCGD 423. Moreover, given the decrease in proliferation elicited by the compound at 6 weeks postinjury, it will be important to ascertain if cells capable of responding are limited in the number of divisions they can undergo as this would suggest that other cell types such as synovium43 may need to be harnessed for cartilage repair or that a therapeutic window exists for potential intervention.…”
Section: Discussionmentioning
confidence: 99%
“…While at a gene expression level there are similarities in the spatial architecture of growth plate and articular cartilage (43), their embryonic origin is distinctly different. Articular chondrocytes are embryonically derived from the interzone cells forming both the synovial lining and the articular cartilage of the joint (44) and in postnatal stages can be distinguished from growth plate chondrocytes by lubricin expression (45). Possibly, the signaling mechanisms are also different between articular and growth plate chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that FLS are not highly proliferative in adulthood. Only a small proportion of the FLS is known to undergo an extremely slow rate of proliferation, similar to that of stem‐like cells . Moreover, it has also been shown that cell proliferation does not play a significant role in TNF‐induced FLS transformation .…”
Section: Discussionmentioning
confidence: 99%